If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15y + 3x = 61 Reorder the terms: 3x + 15y = 61 Solving 3x + 15y = 61 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15y' to each side of the equation. 3x + 15y + -15y = 61 + -15y Combine like terms: 15y + -15y = 0 3x + 0 = 61 + -15y 3x = 61 + -15y Divide each side by '3'. x = 20.33333333 + -5y Simplifying x = 20.33333333 + -5y
| 0=-16t^2+24t+40 | | 4+2q=8 | | 5n+3=4-6(6-5n) | | p+(-9)=8 | | 10=3y+1 | | -14-8k=2k+8k | | 3x=x^2+9 | | 50=x(x*0.16) | | -12+5m+10=2m-10-m | | (15/28)/35 | | t/7=-9/1 | | 8r-5q=3forq | | -d+7= | | 13x+1+12x+9= | | t/t=-9/1 | | 10x-4-6x=-84 | | 9x-81=7 | | .3+.6=.06 | | 4/24 | | (-6)(-6)= | | 24/.4 | | 19=3t-23 | | 3(3m+4)-2(m-7)=0 | | 6d-18+2=2 | | 24/.04 | | 12x+12x+16+10x-4=102 | | -20=-4q | | b^3+15b^2-904=0 | | -10t=90 | | 0.4/24 | | [7-2y]-8=-3 | | 2x^2-22x-12=0 |